Social Science - Based Learning Innovation Strategy in Primary School Social Inquiry - Syahnur , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This study dilator background in teaching social studies in elementary school teacher is less build/ develop students' sense sensitive social issues, less invites students to formulate problems, lack invite students to formulate answers while, and less invite students to collect data, less invites students to test the temporary answer and formulating conclusions. This study aimed to describe the increase in social studies learning process by using the strategy of social inquiry. This type of research that is carried out classroom action research (PTK), using a qualitative approach and quantitative approach. Research subjects teacher and fifth grade students of SD Negeri 31 Lubuk Alung. This study consisted of two cycles 1 cycle two meetings and two one session. Research procedures including planning, implementation, observation and reflection The results showed observation of the lesson plan in the first cycle 1 score of 75% meeting the qualification enough, cycle 1 meeting two good qualifying score of 85%, while the second cycle increased by 92% score excellent qualifications. Conduct observations on aspects of teacher learning cycle I encounter one qualifying scores obtained 75% good, and cycle 1 meeting 2 qualifying score of 86% is very good. Cycle 2 increased 90% with excellent qualifications. In the aspect of the first cycle of students meeting one qualifying score of 76% with fairly, in cycle 1 meeting II scores increased by 86% with a qualified sanagt well. In cycle 2 increased by 93% with excellent qualifications. For student learning outcomes I cycle 1 score 70.83 meeting with a good qualification, and at cycle 1 meeting 2 scores increased 79.68 with excellent qualifications. 2 cycles of learning outcomes skort meeting increased 85 with excellent qualifications. Thus Social Inquiry Strategy can improve student learning outcomes in social studies learning in class V SDN 31 Lubuk Alung Padang Pariaman